3D Self‐Architectured Steam Electrode Enabled Efficient and Durable Hydrogen Production in a Proton‐Conducting Solid Oxide Electrolysis Cell at Temperatures Lower Than 600 °C. Issue 11 (31st August 2018) - Wu, Wei; Ding, Hanping; Zhang, Yunya; Ding, Yong; Katiyar, Prashant; Majumdar, Prasun K.; He, Ting; Ding, Dong
Abstract: Hydrogen production via water electrolysis using solid oxide electrolysis cells (SOECs) has attracted considerable attention because of its favorable thermodynamics and kinetics. It is considered as the most efficient and low‐cost option for hydrogen production from renewable energies. By using proton‐conducting electrolyte (H‐SOECs), the operating temperature can be reduced from beyond 800 to 600 °C or even lower due to its higher conductivity and lower activation energy. Technical barriers associated with the conventional oxygen‐ion conducting SOECs (O‐SOECs), that is, hydrogen separation and electrode instability that is primarily due to the Ni oxidation at high steam concentration and delamination associated with oxygen evolution, can be remarkably mitigated. Here, a self‐architectured ultraporous (SAUP) 3D steam electrode is developed for efficient H‐SOECs below 600 °C. At 600 °C, the electrolysis current density reaches 2.02 A cm −2 at 1.6 V. Instead of fast degradation in most O‐SOECs, performance enhancement is observed during electrolysis at an applied voltage of 1.6 V at 500 °C for over 75 h, attributed to the "bridging" effect originating from reorganization of the steam electrode. The H‐SOEC with SAUP steam electrode demonstrates excellent performance, promising a new prospective for next‐generation steam electrolysis at reduced temperatures. Abstract : A self‐architectured ultraporous (SAUP) 3D steam electrode is applied in a proton‐conducting electrolysis cell. The solid oxide electrolysis cell demonstrates remarkable steam electrolysis efficiency below 600 °C, attributed to highly improved mass transfer and increased active reaction area within the 3D electrode, as well as the interface reorganization under operation conditions. This SAUP structure would find wide applications in electrochemical energy conversion and storage systems.